Influence of nanosilica on moisture resistance of polymer modified bitumens - Bala, N. (Taylor and Francis Inc., 2018)
In this research, the effects of nanosilica and polymer on moisture resistance and other properties of hot mix asphalt have been investigated. The asphalt binder was modified using polyethylene and polypropylene polymers with varying percentages of nanosilica. The Marshall stability, flow, indirect tensile strength, stiffness modulus and resistance to moisture damages test tensile strength ratio (TSR) and retained Marshall stability (RMS) tests were conducted. The results show that application of nanosilica improves the stability, reduces optimum binder content, increases stiffness as well as strength characteristic of the asphalt mixtures. Moisture damage analysis of the modified mixtures shows a good enhancement due to addition of nanosilica particles. Â© 2018 Taylor & Francis Group, LLC.